2016
DOI: 10.1093/mnras/stw2889
|View full text |Cite
|
Sign up to set email alerts
|

Filamentary flow and magnetic geometry in evolving cluster-forming molecular cloud clumps

Abstract: We present an analysis of the relationship between the orientation of magnetic fields and filaments that form in 3D magnetohydrodynamic simulations of cluster-forming, turbulent molecular cloud clumps. We examine simulated cloud clumps with size scales of L ∼ 2-4 pc and densities of n ∼ 400-1000 cm −3 with Alfvén Mach numbers near unity. We simulated two cloud clumps of different masses, one in virial equilibrium, the other strongly gravitationally bound, but with the same initial turbulent velocity field and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 109 publications
6
28
0
Order By: Relevance
“…A clear decreasing trend in the ∆θ vs. F 8µm relation is found as: with the correlation coefficient R=0.63; further indicating that the magnetic field surrounding the expanding Hii regions becomes to follow the outlines of the expanding shells and is approximately parallel to the ionization (or shock) front. In numerical simulations of expanding Hii regions, a shell of material is swept up as the Hii region grows and the magnetic field inside the shell is approximately parallel to the ionization front (Arthur et al 2011;Klassen, Pudritz & Kirk 2017), which is consistent with our findings here.…”
Section: Compressed Magnetic Field Due To Stellar Feedback From Expansupporting
confidence: 90%
See 2 more Smart Citations
“…A clear decreasing trend in the ∆θ vs. F 8µm relation is found as: with the correlation coefficient R=0.63; further indicating that the magnetic field surrounding the expanding Hii regions becomes to follow the outlines of the expanding shells and is approximately parallel to the ionization (or shock) front. In numerical simulations of expanding Hii regions, a shell of material is swept up as the Hii region grows and the magnetic field inside the shell is approximately parallel to the ionization front (Arthur et al 2011;Klassen, Pudritz & Kirk 2017), which is consistent with our findings here.…”
Section: Compressed Magnetic Field Due To Stellar Feedback From Expansupporting
confidence: 90%
“…In numerical simulations, the magnetic field strength is enhanced by a factor of about 5 to 6 in the compressed shell when comparing the magnetic field strength inside the expanding Hii regions (Klassen, Pudritz & Kirk 2017). If we adopt the same enhancement factor, the magnetic field strength inside the expanding Hii regions ("B" and "C") should be ∼200 µG.…”
Section: Compressed Magnetic Field Due To Stellar Feedback From Expanmentioning
confidence: 98%
See 1 more Smart Citation
“…Filamentary structures exist in molecular clouds, with sizes ranging from a few to tens of parsecs (André et al, 2014;Wang et al, 2016). Recent magnetohydrodynamic (MHD) simulations (Klassen et al, 2017;Li et al, 2018;Gómez et al, 2018) probing the formation of large-scale filamentary clouds suggest a complex evolutionary process involving the interaction and fragmentation of dense, velocity-coherent, fibers into chains of cores, resembling observations in nearby clouds (e.g., L1495/B213 and Musca cloud; Hacar et al, 2013Hacar et al, , 2016. The simulations show that global magnetic fields are expected to be roughly perpendicular to the longer axes of dense filamentary clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Several velocity coherent fibers are identified inside the clouds and appear to be supportable along the main filament. In 3D MHD simulations of cluster-forming turbulent molecular cloud clumps, Klassen et al (2017) found that B-fields are oriented parallel to sub-virial clouds and perpendicular to denser gravitationally-bound clouds.…”
Section: Introductionmentioning
confidence: 99%